Evaluation of berberine as a natural compound to inhibit peach brown rot pathogen Monilinia fructicola. (January 2017) - Fu, Weihui; Tian, Geran; Pei, Qinghui; Ge, Xizhen; Tian, Pingfang
Abstract: Berberine (BBR) is a traditional antidiarrheal compound with excellent safety profiles. Our previous study reported that BBR strongly inhibited brown rot pathogen Monilinia fructicola . In this study we assess its potential commercial performance. We found that the spore germination and mycelial growth of M . fructicola could be totally inhibited in vitro by BBR at 4.10 μg ml −1 and 45.50 μg ml −1, respectively, suggesting the strategy of spraying BBR prior to hyphal growth. Next, we compared the 50% effective concentration (EC50 ) and minimal inhibitory concentration (MIC) of BBR with those of synthetic chemical fungicides, and results showed that BBR is economically viable to manage brown rot disease. Strikingly, although M . fructicola was successively treated by BBR for sixteen generations, the EC50 and MIC values remained nearly unchanged, and no mutation occurred in the genes that confer resistances to chemical fungicides, indicating that M . fructicola is less likely to develop resistance to BBR. Furthermore, two years of field trials showed that BBR effectively controlled peach brown rot and no visual damage was observed on leaves and fruits. Given its well-known safety, high efficacy and prolonged activity, we believe that BBR is a promising natural fungicide to control brown rot disease. Highlights: Compared with mycelial growth, spore germination of Monilinia fructicola is easier to be inhibited by berberine. Berberine is economically viable to manage brown rot disease. M. fructicola is hard to develop resistance to berberine. Berberine can control peach brown rot and has no damage on leaves and fruits.